Work, Identity, Place, and Population. A Changing Landscape - Bennett, Julia (Frontiers in Sociology, 2020)
Taking a biographical approach, this paper uses life history narratives across four generations of families living and working in Wigan, Lancashire to analyse social and cultural changes in working life biographies over the past 80 years. Beginning with those who left school at 14, prior to the 1944 Education Act up to the present, where young people are required to remain in education until 18, the paper examines the decisions people have taken throughout their working lives. Inevitably these are shaped by structural changes, particularly to the industrial landscape. The biographical narratives allow a ‘bottom up’ approach to uncovering changes to life courses over three generations in a northern British former industrial town whilst also exploring the wider relations between self, society and place (conceptualised here as ‘taskscape’) in a post-industrial setting. Key changes over the generations are the increased ability of women to pursue careers in addition to having a family, the decrease in parental influence over career choice, and the loss of a ‘job for life’ and employment opportunities for manual workers.